(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
This article emphasizes the importance of consumer loyalty for modern business; considers customer loyalty as a tool to increase individualization of the consumer and as one of the most powerful marketing communications tools that helps attract new customers.